Effects of School Absences on GPAs for Disabled Students - Elizabeth Christani; Laura Revetti; Ashleigh Sue Young; Karen H Larwin (Institute of Advanced Engineering and Science, 2015)
Chronic absences, suspensions, and expulsions can all be detrimental to students’ GPAs. Students with disabilities have a disadvantage with learning and require additional services making it crucial that they are present in school. There are various reasons why students miss school and the study examined a few specific research questions. The current investigation examined students’ current GPA scores in the core content areas compared to the number of days absent from school, the frequency of health related school absences, and the number of days spent out of school due to suspensions and expulsions, using data from a national data set. This investigation examines whether or not attendance is related to students’ academic success, when specifically considering students with identified disabilities.